Bio-Based Polymers for Engineered Green Materials - Schnabel, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
With daily signals, Nature is communicating us that its unconscious wicked exploitation is no more sustainable. Our socio-economic system focuses on production increasing without considering the consequences. We are intoxicating ourselves on a daily bases just to allow the system to perpetuate itself. The time to switch into more natural solutions is come and the scientific community is ready to offer more natural product with comparable performance then the market products we are used to deal with. This book collects a broad set of scientific examples in which research groups from all over the world, aim to replace fossil fuel-based solutions with biomass derived materials. In here, some of the most innovative developments in the field of bio-materials are reported considering topics which goes from biomass valorization to the synthesis of high preforming bio-based materials.